Technology readiness of medical students and the association of technology readiness with specialty interest - Wyatt MacNevin (Canadian Medical Education Journal, 2021)
Background: Technology readiness (TR) is a construct which characterizes an individual’s propensity to utilize new technology. Despite increased technology use in healthcare, limited data exists on medical student TR and the relation of TR with specialty interest. This study assesses the TR of 2nd year medical students and its association with specialty interest.